Simple Solutions During Distance Learning - Kovács, Cintia; Námesztovszki, Zsolt (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Distance learning has become a very popular concept these days. To put it simply, distance learning means (skoll.hu, 2021) passing on some knowledge and information via internet and then asking them to report when the teacher and the student do not physically meet, only in the online environment. In technical terms, we have plenty of distance learning opportunities. Which one we choose is a matter of our prior knowledge, experience and skills, on the one hand, on the other hand the time and financial framework for building the system. The second half of the 2019/2020 school year did not start most easily, education suddenly changed enormously. Many educators and students have faced a new challenge: the school year continues in distance learning. Online learning is thus no longer just a “trendy” form of learning, but has become pretty much the only one option during the pandemic. The lecture presents some simple steps and methodological solutions that can facilitate the work of a teacher teaching in quarantine.